Lehninger principles of biochemistry - Lehninger, Albert L. (W.H. Freeman, 2005)
Lehninger Principles of Biochemistry, Fourth Edition brings clarity and coherence to an often unwieldy discipline, while incorporating the field's most important recent developments and applications.